Reliability model for a distribution system incorporating snowfall as a severe weather event - Chaudhuri, Tanaya (2015)
Distribution system reliability assessment is essential to ensure reliable power supply to customers by predicting the availability of power supply and taking regulatory actions that the situation demands. Reliability assessment demands thorough study of failure rate nature. In the past, studies have been made on climate based failures due to wind and lightning, but snowfall event which is the growing reason behind power failures today, remains untouched. This paper analyses distribution system’s reliability degradation due to snowfall event. A model is derived to find the failure rate due to heavy snowfall and then due to some major severe weather events considered together. A mathematical relation between the power failure rate and the snowfall rate is analytically estimated confirming to measured data. The reliability assessment of an existing power system has been done on a seasonal basis.